A Promising Vector for TCR Gene Therapy: Differential Effect of siRNA, 2A Peptide, and Disulfide Bond on the Introduced TCR Expression - Sachiko Okamoto; Yasunori Amaishi; Yumi Goto; Hiroaki Ikeda; Hiroshi Fujiwara; Kiyotaka Kuzushima; Masaki Yasukawa; Hiroshi Shiku; Junichi Mineno (Elsevier, 2012)
Adoptive immunotherapy using TCR gene-modified T-lymphocytes is an attractive strategy for targeting malignancies. However, TCR mispairings between endogenous and introduced TCR chains are a major concern, as they may induce mixed TCRs with unknown specificities and may reduce the expression of therapeutic TCRs. To overcome these problems, we have recently established a novel retroviral siTCR vector encoding small-interfering RNAs (siRNAs) to knockdown endogenous TCR genes for the efficient expression of therapeutic TCRs. In this study, to improve the efficacy of siTCR vectors, we developed 2A peptide-based siTCR vectors that could increase the expression levels of transduced TCRs compared with internal promoter-based siTCR vectors. We also evaluated the efficacy of an siTCR strategy and the addition of a new interchain disulfide bond created by cysteine modification. We found that the effect of the cysteine modification depended on TCR variations, while the siTCR strategy improved the expression of all TCRs tested. Furthermore, the combined effect of the siTCR and cysteine modification strategies was highly significant for certain TCRs. Therefore, our novel siTCR technology, in isolation or in combination with another strategy, may open the door to effective immunotherapy for cancer patients.